EVALUASI KELAYAKAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN DIGITAL MENGGUNAKAN KERANGKA SECTIONS PADA ASPEK EASE OF USE, INTERACTION, DAN SECURITY - Ilmy Yasmin Huwaida; Nadia Putri Diana; Lutfiatul Jannah; Alya Safira; Hesti Kusumaningrum (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
ABSTRACT The development of information technology in the digital era has driven changes in the learning process, particularly through the use of online learning platforms. One platform widely used in learning activities is Google Classroom because it can facilitate the delivery of materials, assignment collection, and communication between teachers and students. This study aims to evaluate the feasibility of using Google Classroom as a digital learning medium using the SECTIONS framework focused on three aspects: ease of use, interaction, and security. A mixed methods approach was used in this study by taking data directly from the field. Data were obtained by distributing questionnaires to 50 respondents consisting of students, university students, and teachers or lecturers who have used Google Classroom. Data were analyzed using descriptive analysis by calculating the average value of each indicator on a four-level Likert scale. In general, in the ever-transforming educational landscape, numerous studies have revealed a crucial truth: Google Classroom is not just a tool, but a truly digital learning medium for crafting more dynamic learning experiences. From classrooms to the corners of homes, this platform has proven its ability to bridge distances, simplify complexity, and open the door to limitless collaboration, carving a positive imprint on every step of the learning process. ABSTRAK Perkembangan teknologi informasi pada era digital telah mendorong perubahan dalam proses pembelajaran, khususnya melalui pemanfaatan platform pembelajaran daring. Salah satu platform yang banyak digunakan dalam kegiatan pembelajaran adalah Google Classroom karena mampu memepermudah pemberian materi, pengumpulan tugas, serta komunikasi antara pengajar dan peserta didik. Penelitian ini bertujuan untuk mengevaluasi kelayakan penggunaan Google Classroom sebagai media pembelajaran digital dengan menggunakan kerangka SECTIONS yang difokuskan pada tiga aspek, yaitu ease of use, interaction, dan security. Pendekatan mixed method digunakan dalam penelitian ini dengan mengambil data langsung dari lapangan. Data diperoleh melalui penyebaran kuesioner kepada 50 responden yang terdiri dari siswa, mahasiswa, serta guru atau dosen yang pernah menggunakan Google Classroom. Data dianalisis menggunakan analisis deskriptif dengan menghitung nilai rata-rata dari setiap indikator pada skala likert empat tingkat. Secara umum, dalam lanskap pendidikan yang terus bertransformasi, berbagai penelitian telah menyingkap sebuah kebenaran penting: Google Classroom bukan sekadar alat bantu, melainkan sebuah media pembelajaran digital yang sungguh layak untuk merangkai pengalaman belajar yang lebih dinamis. Dari ruang-ruang kelas hingga sudut-sudut rumah, platform ini telah membuktikan kemampuannya dalam menjembatani jarak, menyederhanakan kompleksitas, dan membuka gerbang kolaborasi yang tak terbatas, mengukir jejak positif dalam setiap langkah proses pembelajaran.